Percepções quanto aos riscos e impactos socioambientais do polo cimenteiro no litoral sul paraibano - Seidel, Monique Alessandra (2017)
The installation of a Cement Industry Pole on the state of Paraíba’s southern coast, a region rich in limestone, economically dependent on tourism, fishing, sugarcane monoculture and family farming, is a significant project in terms of public support and also in generation of environmental impacts, yet little publicized or studied. The factories installation is perceived in several ways by the population: Positively, when linked to the expectation of job creation and economic development of municipalities; with distrust by those who fear environmental degradation, impacts on the landscape and land use. This, of course, is also related to the various factors that influence the perception of different social actors. In order to evaluate these points of view and to gather more data on the south coast’s cement industry, a qualitative research was carried out in which it was sought to reach insights on the risks and impacts of the arrival of these factories, on the interaction between important social actors in this context, as company, managers, government and community and their actions in this process. For this, it was necessary to support an interdisciplinary theoretical framework, which included the perception of risks and impacts of cement production. The results show that the actors major concern is the water pollution risk or the competition among the hydric resources, in addition to the risk of damage to human health caused by air pollution. They also demonstrate widespread dissatisfaction to corporate communication, directly related to a lack of trust in institutions and to past environmental and territorial conflicts. All this amid the economic and social insecurity caused by the current political context.